PROTECTIVE BEHAVIOR AGAINST COVID-19 AMONG VIETNAMESE PEOPLE IN THE SOCIAL DISTANCING CAMPAIGN: A CROSS-SECTIONAL STUDY - Lê, Vũ Đình Phi (Trường Đại học Đà Lạt, 2023)
In the global fight against the rapid spread of COVID-19, a variety of unprecedented preventive measures have been implemented across the globe, as well as in Vietnam. How Vietnamese people respond to threats to their health and life remains unclear. For this reason, the current study aims to examine Vietnamese people’s protective behavior and its factors. Based on 1,798 online survey respondents’ data collected on the last three days of the nationwide social distancing campaign in mid-April, it is found that gender, knowledge of COVID-19 and preventive measures, and attitudes towards the COVID-19 prevention policies are the three main factors of participants’ protective behaviors. We also find that males are less likely than females to adopt precautionary measures. People who are knowledgeable about COVID-19 may have inappropriate practices towards it. Further research is needed to examine other determinants of protective behaviors to provide more useful information for authorities, public health policy-makers, and healthcare workers to deliver the best practices to control COVID-19 in our country.